Recycled Rubber Fiber Reinforced Bearings (RR-FRBs) as base isolators for residential buildings in developing countries: The demonstration building of Pasir Badak, Indonesia. (1st August 2019) - Calabrese, A.; Losanno, D.; Spizzuoco, M.; Strano, S.; Terzo, M.
Highlights: RR-FRBs are extremely light-weight and low-cost. RR-FRBs could be widely employed as an effective seismic risk mitigation technology. The performances of RR-FRBs are generally as good as those of conventional devices. Response of RR-FRBs base isolated building match those obtained with FPS and LRB. Results of RHAs show a significant reduction of the seismic demand in the structure. Abstract: The aftermath of the Mw 7.1 Central Mexico earthquake struck at 13:14 CDT on 19 September 2017 confirmed, once again, the need of introducing seismic mitigation technologies that can effectively be implemented on a wide scale to reduce the seismic risk in developing regions of the world. With this in mind, the aim of this paper is the validation of Recycled Rubber-Fiber Reinforced Bearings (RR-FRBs) as base isolation devices for low-cost houses in developing counties. Results of Response History Analyses (RHAs) of a RR-FRBs base isolated residential building are discussed in this work, together with the design, Finite Element Analyses (FEAs), manufacturing and testing of full-scale prototype bearings for the building under investigation. In addition, the seismic performance of the RR-FRBs base isolated structure is compared to the response of the same building when isolated at the base with conventional devices, namely Laminated Rubber Bearings (LRBs) and Friction Pendulum Systems (FPSs). Results of this work underline the high potential of these low-cost bearings as base isolation devices for residential buildings, confirming the possibility of achieving a significant improvement of the seismic performance of ordinary structures by using the low-cost and easy to manufacture RR-FRBs.